The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/(sici)1096-8628(19990115)82:2<149::aid-ajmg10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of chromosomal abnormalities at amniocentesis: Over 20 years of cytogenetic analyses in one laboratory

Abstract: Prenatal diagnosis of chromosomal disorders has been performed for more than 20 years, mainly for advanced maternal age. Chromosomal abnormality rates derived from second trimester amniocentesis have mainly come from a collection of small-scale studies from North America and Western Europe. Accurate risk estimates for chromosomal abnormalities are important tools for the physician or obstetrician who would need to make referrals to a prenatal genetic center. This paper presents amniocentesis rates of clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 14 publications
3
22
0
3
Order By: Relevance
“…The results of fetal cytogenetic abnormalities in our study are similar to those reported in the literature (Caron et al, 1999;Carothers et al, 1999;Quintana et al, 1999). Several studies have shown that Down syndrome is the most common and clinically significant cytogenetic abnormalities detected in prenatal cytogenetic studies (Mathews et al, 1992;Carothers et al, 1999), followed by Edwards Syndrome (Song et al, 1997;Han et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…The results of fetal cytogenetic abnormalities in our study are similar to those reported in the literature (Caron et al, 1999;Carothers et al, 1999;Quintana et al, 1999). Several studies have shown that Down syndrome is the most common and clinically significant cytogenetic abnormalities detected in prenatal cytogenetic studies (Mathews et al, 1992;Carothers et al, 1999), followed by Edwards Syndrome (Song et al, 1997;Han et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…
Prenatal diagnosis with cytogenetic analysis has been recognized for more than 20 yr as a safe and reliable method for couples at increased risk of giving birth to a child with a clinically significant chromosomal abnormality [1,2]. Until Background : Since amniocentesis made prenatal diagnosis feasible in 1967, the method has become a popular tool in obstetric practices.
…”
mentioning
confidence: 60%
“…In the majority of the cases, the parents chose to terminate the pregnancy. The risk of phenotypic abnormality is very low when balanced chromosome rearrangement is inherited from a phenotypically normal carrier parent (Caron et al, 1999); however, some parents may choose to terminate the pregnancy voluntarily if they have concerns regarding future fertility problems for their child.…”
Section: Discussionmentioning
confidence: 99%